The skip-octree: a dynamic cloud storage index framework for multidimensional big data systems. (2015) - Dong, Yunyun; He, Jing; Yao, Shaowen; Zhou, Wei
Nowadays the information explosion have generated a large amount of data. To utilise these data, there is a trend of setup efficient data index, especially for multidimensional data indexing. However, most of the current cloud storage systems build data indexing based on the distributed hash (DHT), where data are stored by the key-value. This module is not very suitable for range queries in multidimensional data indexing. To solve these problems, this paper builds a multidimensional data index based on skip lists and octree structure. Firstly, this architecture adopts the structure of octree to store data and establish the corresponding index mechanism, it can make use of the idea of different dimensional space partitioning to achieve a multi-dimensional index. Secondly, the relevant algorithms are designed to sustain the characteristics of this framework in this paper. Finally, the simulation experiment shows that the skip-octree architecture is feasible and efficient.